Nomadic New Women Exile and Border-Crossing between Spain and the Americas, Early to Mid-Twentieth Century - Silverman, Renée M.; Sánchez-Pardo, Esther (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XV, 362 p. 3 illus., 1 illus. in color.